Pengaruh Kepemimpinan Visioner dan Budaya Kerja terhadap Kinerja Asn di Bappeda Kota Gorontalo - Indriani Iskandar Hiola; Sulila, Ismet; Abdussamad, Zuchri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
BAPPEDA (Development Planning Agency at the Sub-National Level) of Gorontalo City aims to become a superior development planning institution with integrity and responsiveness to community needs. However, despite efforts to implement visionary leadership and foster a positive work culture, the expected outcomes have not been fully achieved. This study examines the effect of visionary leadership on the performance of civil servants (ASN) at BAPPEDA Gorontalo City, the effect of work culture on ASN performance, and the simultaneous effect of visionary leadership and work culture on ASN performance. The study employed a quantitative method with a population of 62 respondents. Data were collected through questionnaires and analyzed using SPSS version 21. The results indicate that visionary leadership has a positive and significant effect on ASN performance, contributing 40.10% to performance improvement. Work culture also has a positive and significant effect on ASN performance, with a contribution of 32.60%. Furthermore, visionary leadership and work culture simultaneously have a significant influence on the performance of ASN at BAPPEDA Gorontalo City. These findings suggest that strengthening visionary leadership and cultivating a positive work culture are important factors in improving employee performance and supporting the achievement of organizational goals.